IbM PETANI UBI KAYU DI KECAMATAN BANGKALA - Halid, Erna; Yassin, Miss Rahma (Jurnal BALIRESO, 2017)
Management of cassava in the village Baroanging, District Bangkala Jeneponto district by farmers are not optimal and do not fully apply the recommended technology innovation so that although productivity is not too low, but still need improvement management, especially the system of cultivation. Cassava plant in the village only be used as plant-stream, but it can help the economy of the community. Because in addition to getting the results of rice crops also get additional income from planting cassava. However, income from farming of cassava is still very low because they only sell in the form of logs, they have yet to diversify the preparations of such products. Though cassava processing easy to do and relatively higher than the price of cassava spindles. One of the diversification of cassava processing is the manufacture of flour Making Flour mokaf mokaf this could be a new business opportunity for cassava farmers. So as to increase the income of cassava farmers. Objectives and targets outcomes to be achieved from the science and technology activities for the public are: 1) the target output short term that will be produced are: (a) Partner skilled in cassava cultivation organic technology use proper cultivation, (b) Partner know the benefits cassava is widely especially benefits flour mokaf, (c) Options were able to produce flour mocaf itself, 2) Target outcomes long term that will be produced are: (a) changing the mindset of farmers, from just farming cassava into the mindset of making these plants be a promising business opportunities, (b) the District Bangkala will be mokaf flour production center, (c) Formed new entrepreneurs that produce flour mokaf. Approach methods are offered to support the realization of the program consists of three methods, namely; (1). Participatory extension, (2) Training (demonstrations and practice activities by participants), (3) Mentoring, coaching the participants by the implementation team, and (4) Mentoring.